Women in the fine arts, from the seventh century B.C. to the twentieth century A.D - Clement, Clara Erskine (Hacker Art Books, 1974)
"WOMEN IN THE FINE ARTS FROM THE SEVENTH CENTURY B.C. TO THE TWENTIETH CENTURY" by Clara Erskine Clement is a historical account written in the early 20th century. The book surveys the contributions of women artists throughout history, spanning over two millennia and across multiple cultures. It aims to highlight women's roles and achievements in the fine arts, pointing out that many artists have been overlooked or forgotten despite their significant contributions. The opening of the book introduces the author's mission to gather information about women artists by reaching out to them directly, thus establishing a foundation of credibility and thoroughness for her work. Clement mentions that over a thousand women artists have been identified for this study, sharing intriguing fragments of history, such as those of ancient Greek and Roman women artist names and highlighting the cultural shifts that impacted their careers. It also critiques the lack of recorded contributions from women in the arts before the Renaissance, outlining the challenges they faced throughout different eras while paving the way for future generations of female artists. The opening sets the stage for a deeper exploration of women's artistic heritage in the following chapters. (This is an automatically generated summary.)
Keywords: arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; thématiques

Pédagogie des opprimés suivi de Conscientisation et révolution - Freire, Paulo (François Maspero, 1974)
Ouvrage majeur de Paulo Freire, ce livre présente quelques aspects d’une pédagogie élaborée non seulement pour les opprimés, mais avec eux, et dans le cadre même de leur lutte perpétuelle pour affirmer leur humanité.
Première publication : 1970 https://web-s-ebscohost-com.proxy.bibliotheques.uqam.ca/ehost/detail/detail?vid=0&sid=4d2dddbb-6f04-4611-9d00-4774e074bd61%40redis&bdata=Jmxhbmc9ZnImc2l0ZT1laG9zdC1saXZl#AN=3149227&db=nlebk
Keywords: approches et analyses; cours; cycles supérieurs; discipline; fem7000; histoire et politique; inégalités; justice sociale; militance; pédagogie; ressource en ligne; systèmes d'oppressions; thématiques; éducation

Our hidden heritage: five centuries of women artists - Tufts, Eleanor (Paddington Press, 1974)
Our hidden heritage: five centuries of women artists unearths an unheralded legacy of art treasures by women artists. THrough individual biographies, the lives and work of twenty-two women artists are authoritatively described by Eleanor Tufts. These exciting portrayals provide new insights into the lives and works, the frustrations and successes of these talented women, as well as into their relationships with their contemporaries, husbands, freinds and families. Over 125 full-page reproductions of their works from major collections throughout the world demonstrate the variety and enduring quality of their art. Their lives and their work were as diverse as their cultures and their times.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; thématiques